Talinum triangulare (Jacq.) Willd. mucilage and pectin in the formulation of ibuprofen microspheres (2022)
Background. Mucilage and pectin are both natural polymers with theadvantages ofavailability and bio¬degradability. Microspheres made from biodegradable polymers can break down naturally after performing their tasks.Objectives. Thestudy aimed touse mucilage and pectin from theleaves ofTalinum triangulare (Jacq.) Willd. aspolymer matrices for theformulation ofmicrospheres, with ibuprofen asthemodel drug.Materials and methods. Both polymers were examined under amicroscope and evaluated using measure¬ments ofviscosity, density, flow properties, swelling power, elemental analysis, Fourier-transform infrared spectroscopy (FTIR), and thedegree ofesterification (DE) for pectin. Themicrospheres were prepared using theionotropic gelation method and alginate:mucilage/pectin atratios of1:1 and 1:2. They were assessed for swellability, drug entrapment effectiveness and drug release profile. Results. Themucilage particles were ovoid while pectin particles were irregularly shaped. Pectin had higher particle, bulk and tapped densities than mucilage, while mucilage had ahigher swelling power and abetter flow than pectin. Talinum triangulare pectin isalow-methoxyl pectin with aDE of7.14%. TheFTIR spectra showed no interaction between thepolymers and ibuprofen. Thesurface morphology ofthemicrospheres without ibuprofen was smooth, while those with ibuprofen revealed aspongy-like mesh. Theswelling power ofthemicrospheres was higher inphosphate buffer with apH of7.2 than indistilled water. Theentrapment efficiency ranged within 39.57–60.43% w/w, with microspheres containing alginate:mucilage/pectin ratio of1:1having higher entrapment efficiency. Microspheres with polymer ataratio of1:1 provided alonger release (>2h), while microspheres with polymer blend of1:2 provided animmediate release ofibuprofen. Conclusions. Thepolymers ofT. triangulare could be used asmatrices inmicrosphere formulations.